2021
DOI: 10.1002/ar.24755
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neuronal cells which contain dopamine β‐hydroxylase, tyrosine hydroxylase, neuropeptide Y and vasoactive intestinal polypeptide in the human internal carotid nerve

Abstract: The human internal carotid nerve (ICN) occasionally has a swelling beneath the external opening of the carotid canal. In this study, the presence and distribution of neuronal cells were investigated in the bilateral ICNs of nine human cadavers. Among 44.4% of the cadavers, swellings were detected in the ICN. Their diameters ranged from 1.7 to 3.6 mm (average ± SD = 2.6 ± 0.7 mm). Thirty‐eight percent of these swellings were large (diameter > 3 mm) and showed an oval shape. The large swelling contained many neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies have immunohistochemically demonstrated the sympathetic and parasympathetic innervation and origin of salivary glands for synthesizing enzymes of neurotransmitters. Sympathetic and parasympathetic nerves contain tyrosine hydroxylase (TH) and choline acetyltransferase (ChAT), respectively, in the cranial and cervical autonomic ganglia (Chiba & Tanaka, 1998; Dibner & Black, 1976; Kawashima et al, 2021; Kokubun et al, 2019; Sato, Yajima, Kokubun, et al, 2022; Suhonen et al, 1993; Wojtkiewicz et al, 2011). In the periphery, the density of TH‐ and ChAT‐containing nerves is different among major and minor salivary glands (Arvidsson et al, 1997; Batbayar et al, 2004; Kawashima et al, 2021; Mateos‐Hernandéz et al, 2020; Sato, Yajima, Kokubun, et al, 2022; Wojtkiewicz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have immunohistochemically demonstrated the sympathetic and parasympathetic innervation and origin of salivary glands for synthesizing enzymes of neurotransmitters. Sympathetic and parasympathetic nerves contain tyrosine hydroxylase (TH) and choline acetyltransferase (ChAT), respectively, in the cranial and cervical autonomic ganglia (Chiba & Tanaka, 1998; Dibner & Black, 1976; Kawashima et al, 2021; Kokubun et al, 2019; Sato, Yajima, Kokubun, et al, 2022; Suhonen et al, 1993; Wojtkiewicz et al, 2011). In the periphery, the density of TH‐ and ChAT‐containing nerves is different among major and minor salivary glands (Arvidsson et al, 1997; Batbayar et al, 2004; Kawashima et al, 2021; Mateos‐Hernandéz et al, 2020; Sato, Yajima, Kokubun, et al, 2022; Wojtkiewicz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic and parasympathetic nerves contain tyrosine hydroxylase (TH) and choline acetyltransferase (ChAT), respectively, in the cranial and cervical autonomic ganglia (Chiba & Tanaka, 1998; Dibner & Black, 1976; Kawashima et al, 2021; Kokubun et al, 2019; Sato, Yajima, Kokubun, et al, 2022; Suhonen et al, 1993; Wojtkiewicz et al, 2011). In the periphery, the density of TH‐ and ChAT‐containing nerves is different among major and minor salivary glands (Arvidsson et al, 1997; Batbayar et al, 2004; Kawashima et al, 2021; Mateos‐Hernandéz et al, 2020; Sato, Yajima, Kokubun, et al, 2022; Wojtkiewicz et al, 2011). TH‐positive nerves are often detected in the submandibular gland and very infrequently in the lingual mucous gland (Sato, Yajima, Tachiya, et al, 2022; Soinila et al, 1991).…”
Section: Introductionmentioning
confidence: 99%